Depression and Obesity in Patients With Psoriasis and Psoriatic Arthritis: Is IL-17-Mediated Immune Dysregulation the Connecting Link? - Zafiriou, Efterpi; Daponte, Athina I.; Siokas, Vasileios; Tsigalou, Christina; Dardiotis, Efthymios; Bogdanos, Dimitrios P. (Frontiers in Immunology, 2021)
Patients with psoriasis are frequently obese and experience anxiety or suffer from depressive disorders. The immunopathogenesis of psoriasis and indeed psoriatic arthritis is largely based on the pivotal role of IL-17/IL-23 axis, to an extent that currently monoclonal antibodies selectively inhibiting IL-17 or IL-23 are routinely used for the treatment of psoriatic diseases. Emerging data, demonstrating a decisive role for IL-17 and IL-17 producing cell subsets, such as Th17 in the induction and progression of obesity and depression has led authors to suggest that psoriatic disease, obesity and anxiety/depression may indeed be interconnected manifestation of a state of immunedysregulation, the linked being IL-17 and its related cells. We discuss this hypothetical link in depth taking into account the beneficial effects anti-IL17 and anti-IL-17 receptor inhibitors in treating psoriatic disease and the on-going debate as to whether these biologics may exert a direct or indirect effect in ameliorating concomitant obesity and depressive disorders, which are frequently noted in the same patient.